Tantangan Implementasi Kearifan Lokal dalam Upaya Mencegah dan Mengatasi Kekerasan Seksual dan Perundungan di Lingkungan Sekolah - Kamilah, Anita; Astuti, Hesti Dwi; Wiharma, Cecep; Aulia, Salsabila Hadi; Azhari Kusworo, Fuji Raihan Azhari; Ramadani, Adit Rizki (Fakultas Hukum Universitas Semarang, 2025)
Sexual violence and bullying in schools are serious and complex issues that negatively affect students’ psychological, social, and academic well-being. A learning environment that should serve as a safe and nurturing space can become harmful if these issues are not addressed appropriately. This community service program, conducted at SMA 1 Pasundan Cianjur, aims to introduce and integrate local Sundanese wisdom values such as silih asih (mutual affection), silih asah (mutual learning), and silih asuh (mutual care) as a cultural approach to preventing sexual violence and bullying in schools. The activities were carried out through seminars and interactive discussions involving students, teachers, and school staff. Data were collected through direct observation and feedback from seminar participants. The results indicate that the majority of students are aware of bullying practices in their school environment, and some reported having experienced or felt concerned about potential incidents of sexual violence or bullying. This program successfully raised awareness of the importance of cultural values as a foundation for character education and child protection within the educational setting. Moving forward, the integration of local wisdom is expected to become part of a sustainable preventive strategy to create a safe, inclusive, and culturally rooted school environment. Keywords: Land Certificate; Trimulyo Community; Socialization.